Retro Fashion Trend Study on Café Chair Design for Generation Z in Surabaya - Vema Ailsa; Imam Santosa (Universitas Medan Area, 2023)
This article delves into the integration of retro fashion trends in chair design within Surabaya's café scene. Employing a descriptive qualitative research approach, this study seeks a profound comprehension of the impact of retro fashion trends on chair design. Data collection methods encompass theory development, observations, interviews, and questionnaire surveys. The analysis is rooted in predefined outcome variables. The study's findings underscore the substantial influence of the retro fashion trend on café chair design in Surabaya. Notably, Generation Z's consumer demand, characterized by heightened consumerism and a penchant for contemporary trends, plays a pivotal role in shaping fashion cycles and lifestyle choices. The enduring appeal of the retro trend, spanning from the 1970s to the present, resonates strongly with Generation Z, especially those who harbor nostalgic inclinations. Furthermore, the adaptation of retro fashion trends remains pertinent as a significant segment of the population still gravitates toward styles from the 1970s to the 1990s. This research reveals that Surabaya's café chair designs adeptly incorporate retro elements, encompassing material selection, silhouettes, colors, and styles. By seamlessly amalgamating these retro elements with contemporary influences, these chair designs effectively captivate consumers, fostering an inviting and appealing ambiance within the café environment.